2018
DOI: 10.1371/journal.pone.0195661
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive variation in the U3R region of the 5' Long Terminal Repeat from diverse HIV-1 strains

Abstract: Functional mapping of the 5’LTR has shown that the U3 and the R regions (U3R) contain a cluster of regulatory elements involved in the control of HIV-1 transcription and expression. As the HIV-1 genome is characterized by extensive variability, here we aimed to describe mutations in the U3R from various HIV-1 clades and CRFs in order to highlight strain specific differences that may impact the biological properties of diverse HIV-1 strains. To achieve our purpose, the U3R sequence of plasma derived virus belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…The HIV-1 5’LTR is ~640 bp in length and the U3 region is located upstream of the transcription start site and is divided into the modulatory (−454, −105), enhancer (−105, −79), and promoter (−78, −1) regions (numbering based on the HXB2 sequence) 49 . The modulator region contains several transcription factor binding sites 50 , the enhancer region contains binding sites for NF-kB family members and the core promoter encodes three binding sites for Sp1 and the TATA box. The HIF binding site is located in a region around the −246 position in the U3 region relative to the start codon, and overlaps with a CCAAT/enhancer binding site (C/EBP binding site US3, HXB2 numbering) 38 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 5’LTR is ~640 bp in length and the U3 region is located upstream of the transcription start site and is divided into the modulatory (−454, −105), enhancer (−105, −79), and promoter (−78, −1) regions (numbering based on the HXB2 sequence) 49 . The modulator region contains several transcription factor binding sites 50 , the enhancer region contains binding sites for NF-kB family members and the core promoter encodes three binding sites for Sp1 and the TATA box. The HIF binding site is located in a region around the −246 position in the U3 region relative to the start codon, and overlaps with a CCAAT/enhancer binding site (C/EBP binding site US3, HXB2 numbering) 38 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the fundamental constitution of the HIV-1 promoter is highly conserved among the various genetic subtypes of HIV-1, within this underlying structural theme, there exist many subtype-specific molecular features that may modulate gene expression considerably from the viral promoter. Such differences are evident in the copy-number and nucleotide sequences of different TFBS especially those of USF, c-Myb, LEF-1, Ets1, NF-AT, Ap-1, NF-κB, and Sp1 binding sites, and regulatory elements such as the TATA box and the TAR element (Jeeninga RE et al, 2000;Mbondji-Wonje C et al, 2018;Montano MA et al, 1997). The critical roles that most of these regulatory elements play in positively regulating the basal and inducible levels of viral transcription have been well documented (Garcia JA et al, 1987;Pereira LA et al, 2000).…”
Section: Subtype-associated Molecular Features May Offer Vital Clues mentioning
confidence: 99%
“…This study was done with a total of 80 contigs obtained from a previously described methodology 1 . Briefly, RNA was extracted from selected plasma derived viruses belonging to subtypes B, C, D, F2 and G, as well as CRF02_AG, CRF01_AE and CRF22_01A1 (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide changes generated from these mechanisms affect the entire viral genome, including its highly structured 5′ end region. Indeed, the HIV-1 genome variability was found to be as much as 23% in the 5′LTR-U3 region, about 10% in the gag/pol genes, and more than 30% in the env gene, with overall differences observed primarily between intra and inter-subtype 1 , 2 . Previous studies have revealed that strain differences may influence transmission, replication, and virulence of HIV-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation